2001
DOI: 10.1046/j.1365-2036.2001.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory and tissue‐protectant drug effects: results from a randomized placebo‐controlled trial of gastritis patients at high risk for gastric cancer

Abstract: Background: The inflammatory process involving Helicobacter pylori‐associated gastritis is thought to lead to epithelial damage and contribute to the development of gastric cancer. Evidence exists from animal and in vitro studies suggesting that tetracyclines have both anti‐inflammatory and tissue‐protectant effects unrelated to their antimicrobial activity. We attempted to modulate components of H. pylori’s inflammatory process by: (i) eliminating the infection; (ii) using tetracycline to alter the host’s rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Forty-seven studies, comprising 2,345,540 patients and over 13,500 events reported the association between anti-inflammatory drug use and the risk of GC, met all of the selection criteria and were included in our meta-analysis (Figure 1) 10-15, 19, 21-29, 33-63. Of these enrolled articles, nine were RCT studies 12, 23, 27, 29, 38, 44, 48, 52, 61, fifteen were cohort studies 15, 24, 26, 28, 33-37, 45, 46, 58-60, 62, and the remaining twenty-three were case-control studies 10, 11, 13, 14, 21, 22, 24, 25, 39-43, 47, 49-51, 53, 54, 56, 57, 63. In our study, there were conducted, respectively, seventeen in North America 13-15, 21, 28, 35-37, 39, 43, 44, 47, 48, 53, 54, 57, 58, seventeen in Europe 11, 12, 27, 33, 34, 38, 40-42, 45, 46, 49, 50, 59, 60, 62, 63, eleven in Asia 22-26, 29, 51, 52, 61, and two in Australia 10, 56.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-seven studies, comprising 2,345,540 patients and over 13,500 events reported the association between anti-inflammatory drug use and the risk of GC, met all of the selection criteria and were included in our meta-analysis (Figure 1) 10-15, 19, 21-29, 33-63. Of these enrolled articles, nine were RCT studies 12, 23, 27, 29, 38, 44, 48, 52, 61, fifteen were cohort studies 15, 24, 26, 28, 33-37, 45, 46, 58-60, 62, and the remaining twenty-three were case-control studies 10, 11, 13, 14, 21, 22, 24, 25, 39-43, 47, 49-51, 53, 54, 56, 57, 63. In our study, there were conducted, respectively, seventeen in North America 13-15, 21, 28, 35-37, 39, 43, 44, 47, 48, 53, 54, 57, 58, seventeen in Europe 11, 12, 27, 33, 34, 38, 40-42, 45, 46, 49, 50, 59, 60, 62, 63, eleven in Asia 22-26, 29, 51, 52, 61, and two in Australia 10, 56.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies that were not adjusted for smoking, alcohol consumption, and BMI (body mass index) were omitted 10, 11, 19, 22, 28, 33, 34, 37, 39, 41, 44-46, 49, 52, 53, 56, 58-60, 62, 63. The remaining studies produced an RR of 0.74 (95% CI, 0.70-0.79), with substantial evidence of decreasing heterogeneity (P=0.043, I 2 = 37%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice and Mongolian gerbils, high salt diet may exacerbate H. pylori -induced gastric cancer [46,50,51]. In mice, this occurs as increased proliferation and elongation of gastric pits, which may also provide more room for H. pylori to colonize [51].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of H. pylori may modify the effect of dietary salt intake on progression in the gastric precancerous process. To address these gaps, we analyzed data from a cohort study conducted in Colombia, South America [46] to estimate the effect of salt intake at baseline on future progression of gastric precancerous lesions in the entire cohort and within subgroups with and without H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%